PENGARUH PEMBERIAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi KasusPT.Samudranesia Tour and Travel Pekanbaru) - Yuni Afriani; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The motivation to havea role important because concerns directly on the human elements of in the organization. The motivation right to be able to advance and develop the organization. In the give motivation to employees, one of the indicator that noticed that the exsitence of, the first time that need to do the company to the provision motivation is pay attention to the existence of employees. The existence of a requiement of the existence of the material employees, associated with the physiological.The purpose of this research is to find out of theinfluence of the provision motivation against the perfomance of the employees PT. Samudranesia Tour and Travel Pekanbaru and from of the from of motivation given PT. Samudranesia Tour and Travel Pekanbaru, as well as a factors whatever influence PT. Samudranesia Tour and Travel Pekanbaru give motivation to employees..The study, namely the research quantitative. The research quantitative is a research used in general wear analysis statistics. While the kind of research used is the kind of research survey, namely research take a sample of one of the population and use kuisioner as atool measurement basic data. Samples on this research is employees PT. Samudranesia Tour and Travel Pekanbaru as much 30 respondents. As for the methods used in this study is the research the descriptive analysis, namely a method trying tto find a picture of through about the data the fact, the events actually about the object research. And to data analysis this research using test of regressing liniear simple, the test the coefficient determinasi dan uji-tKey words : Giving motivation and employee perfomance